2021
DOI: 10.1245/s10434-021-11209-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Changes in Breast Cancer Care and Well-Being During COVID-19: A Mixed Methods Study

Abstract: Background Widespread healthcare restructuring due to the COVID-19 pandemic led to modifications in the timing and delivery of care for breast cancer patients. Our study explores patient concerns relating to COVID-19, breast cancer, and changes to breast cancer care. Patients and Methods Breast cancer patients who presented for surgical consultation at an academic, multidisciplinary clinic completed the electronically distributed validated COVID-19 Impact and Healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…In our study, the proportion of patients who reported experiencing sadness or depression was 30.7%, which was consistent with previous ndings. However, according to survey studies and literature review, the incidence of anxiety or depress among cancer patients in other western countries during COVID-19 pandemic was about 33.5% to 47% [14,21,22]. Although Chinese cancer patients might experience less psychological distress compared with patients from western countries, they still need more professional psychosocial support which has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the proportion of patients who reported experiencing sadness or depression was 30.7%, which was consistent with previous ndings. However, according to survey studies and literature review, the incidence of anxiety or depress among cancer patients in other western countries during COVID-19 pandemic was about 33.5% to 47% [14,21,22]. Although Chinese cancer patients might experience less psychological distress compared with patients from western countries, they still need more professional psychosocial support which has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…To better evaluate and address cancer survivors' needs during this special period, health-related quality of life (HRQoL) had been applied to comprehensively assess the level of symptoms, wellbeing and perceived bene ts or concerns in many countries [11,12]. In 2020, MD Anderson Cancer Center (MDACC) developed a 'COVID-19: Impact of The Pandemic and HRQoL in Cancer Survivors (COVID-19 IHRQOL)' questionnaire to speci cally investigate the level of cancer related HRQoL during the pandemic(ClinicalTrials.gov NCT04447222), which had been translated into many other languages after publication [13][14][15]. Due to socioeconomic disparities in different countries, the levels of HRQoL among cancer patients during COVID-19 pandemic were found to be associated with different factors such as treatment delay, lower level of physical activities and so on [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, data collection was interrupted due to COVID-19 pandemic. In addition, considering the effects of the pandemic on cancer patients and caregivers’ psychosocial wellbeing ( Dhada et al, 2021 ; Ludwigson et al, 2022 ), couples recruited after the first lockdown were considered intrinsically different and therefore were not included in the present contribution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the pandemic affects availability and accessibility of healthcare very intensively, inducing moral distress for healthcare providers [ 3 ] and decisional problems for patients. For example, during the COVID-19 pandemic patients and caregivers experienced delays [ 4 ] and treatment modifications in various clinical settings [ 5 , 6 ] that negatively affected their psychological wellbeing and caused decisional conflicts. Shared decision making (SDM) rapidly became challenging during the pandemic, and affected various participants in healthcare processes to a different extent.…”
Section: Introductionmentioning
confidence: 99%